Power feasibility of a low power consumption solar tracker - Ahmad, Salsabila; Shafie, Suhaidi; Ab Kadir, Mohd Zainal Abidin (Elsevier, 2013)
This paper discusses on the generated power and the power consumption of an open-loop time and date based sun positioning solar collector system under three weather conditions; sunny and clear day, cloudy day and heavy overcast and rainy day under Malaysian tropical climate at location E100°11’, N6°26’, The two-axes tracking system used a Programmable Logic Controller (PLC) to maneuver a photovoltaic solar module based on 10° altitude angle tracking and 1° azimuth angle tracking. The daily percentage of power consumed during a clear and sunny day from the tracking motors and controller is 0.05% and 5.84%, respectively. Overall, the system consumed 5.89% of the total generated power.